The 2019 Portuguese general elections - Fernandes, Jorge (2020)
The 2019 Portuguese general elections have led to the formation of another minority government of the Socialist Party. Right-wing parties suffered a resounding defeat. The election had two key consequences. First, after four years of contract parliamentarism with an extreme-left party, the Socialists returned to their historical position of pivotal party in the system. Socialist leader Costa refused to replicate alliances with parties to his left. Second, the 2019 election witnessed the emergence of three new parties, Chega, Iniciativa Liberal and Livre. The election of Chega marks a watershed moment in Portuguese democratic history, as for the first time an extreme-right populist party has gained representation in the country.